The biosynthesis of galactolipids in chloroplast envelopes : a thesis for the degree of Master of Science in Biochemistry - Benny, Athol Graeme (Massey University, 1979)
The procedure of Douce et al (1973) was employed for the isolation of envelopes from purified chloroplasts of spinach (Spinacia oleracea) and maize (Zea maize var. Wis. 235). Maize chloroplasts gave very low yields of envelope protein and low incorporation of radioactivity from UDP-14C-Galactose into galactolipids. However the use of spinach chloroplasts resulted in higher yields of envelope protein and high levels of a galactosyltransferase that synthesised galactolipids from endogenous lipid substrates and added UDP-14C-Galactose. The products of galactosyltransferase were identified as MGDG and DGDG by comparison with standard lipids on thin layer chromatography. The procedure for the isolation of chloroplast envelopes reported by Poincelot and Day (1973) gave a higher yield of less contaminated envelope membranes and an increased specific activity of galactosyltransferase compared to the results obtained using envelopes isolated by the method of Douce et al (1973) Total incorporation of radioactivity from 0.3 μM UDP-14C-Galactose by galactosyltransferase was dependent on the time and temperature of incubation and the nature of the incubation buffer. Maximum incorporation (about 72% of the added radioactivity) was obtained upon incubation at 30°C for 30 min, in 50 mM HEPES-NaOH at pH 8.0. MGDG was identified as the major labelled lipid (MGDG:DGDG ratio 1.7:1). Lower pH values gave higher incorporation into DGDG. A cation dependence of galactosyltransferase was observed and incorporation was stimulated by addition of Ca2+, Mg2+ or Ba2+. Maximum incorporation was obtained with 5 mM Ba2+. In contrast 5 mM Cu2+ completely inhibited incorporation. The sulphydryl nature of the chloroplast galactosyltransferase (Chang, 1970; Mudd et al 1971) was confirmed with galactosyltransferase of the chloroplast envelope. Linoleic acid at 0.72 μM completely inhibited transferase activity. The inhibition by linoleate could be partially removed by addition of about 10 mM Ca2+ or Ba2+ but 10 mM Mg2+ and BSA (30 μg per ml) were without effect. UMP, UDP and UTP at 1 mM inhibited incorporation by transferase. UDP was the most effective inhibitor and gave 50% inhibition of incorporation at about 5 μM. NADH and PPi did not significantly affect incorporation. The addition of exogenous diacylglycerol (1-palmitoyl, 2-oleoyl glycerol or 1, 2-di-linoleoyl glyerol) did not increase the incorporation of radioactive galactose into galactolipids. Incorporation was inhibited by 0.3% Triton X-100 and 6 mM sodium cholate. No radioactivity from added 14C-diacylglycerol was incorporated into MGDG by chloroplast envelopes. Preincubation of the chloroplast envelopes with phospolipase C or D reduced the total amount of radioactivity incorporated by galactosyltransferase. Transferase activity was detectable after preincubation of the envelopes with trypsin and protease. The fatty acid composition of MGDG, DGDG and DG from whole tissue, chloroplasts and chloroplast envelopes of spinach is presented. The characteristic highly unsaturated nature of the fatty acids of MGDG and DGDG is in contrast to the relatively saturated fatty acid content of DG isolated from whole tissue and chloroplasts. However, DG isolated from chloroplast envelopes contained predominantly 16:0, 18:1 and 18:3.
Keywords: Chloroplasts; Galactolipids; Membranes (Biology)